1977
DOI: 10.21273/jashs.102.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium and Phosphorous Fertilization on Quality of Sweet Potatoes1

Abstract: Potassium applications from 0 to 140 kg/ha at 4 locations had more influence on quality of sweet potatoes than P applications of 0 to 73.9 kg/ha as an average of years and locations. As the rate of K but not P applications increased, percent dry matter decreased. K and P applications reduced protein content and firmness of canned roots. K slightly increased the crude fiber content (dry wt basis) of the roots, whereas P applications had no affect on fiber content. K and P fertilization had no influence on carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Dry matter content of some sweet potato cultivars was not influence by fertilizers (2). In other research, dry matter content decreased with an increase level of K (3,4). Potassium level did not influence weight loss in storage ( 4), but increased N has been associated with greater weight loss (13).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Dry matter content of some sweet potato cultivars was not influence by fertilizers (2). In other research, dry matter content decreased with an increase level of K (3,4). Potassium level did not influence weight loss in storage ( 4), but increased N has been associated with greater weight loss (13).…”
mentioning
confidence: 67%
“…Modem high density plantings require careful management in order to control tree size and maintain productivity. Summer pruning is presently being promoted by some pomologists as an aid to control tree vigor (2,5,10,12,15), to increase fruit bud formation (5,10,11,12), and to improve fruit quality (3,4). Earlier research indicated summer pruning was too devitalizing and laborious to be of commercial value (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When S was the limiting element in soil, uptake of N by com (13) and other grains (5,14) was controlled by amounts of available S. The effect of S on the N content of sweet potatoes has not been reported. Potassium has been observed to produce a linear yield response in sweet potatoes (3,6). Increased yield, 'Received for publication Dec. 20, 1980; paper no.…”
mentioning
confidence: 99%
“…High rates of nitrogen increase root cracking (10,14), decay and weight loss during storage of the roots (10), and de crease flesh color with increases in pro tein and firmness of canned products (3). Phosphorus did not increase sweet potato yield on continuously cropped soils (13) or influence dry matter, carotenoids, crude fiber, and splits of canned products but did decrease firmness and protein lev el (2). Potassium has been reported to in crease yield and cracking (4) with a re duction of dry matter and firmness of the canned product (2,4) but not influence carotenoids or splitting (2).…”
mentioning
confidence: 99%